Comparison of Postpartum Depression, Psychological Distress, Resilience, and Psychological Well-Being between Fathers with Infants Admitted to the Neonatal Intensive Care Unit and Fathers with Healthy Infants - H Khoshi; A Hamidia; M Ahmadpour-Kacho; M Haghshenas Mojaveri; H Gholinia; M Faramarzi (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul)
Background and Objective: Most new fathers experience a lot of stress when their newborn is admitted to the Neonatal Intensive Care Unit (NICU). However, most studies have focused on the needs of mothers. The aim of this study is to compare postpartum depression, psychological distress, resilience, and psychological well-being in new fathers of infants admitted to the NICU and fathers of healthy infants. Methods: This case-control study was conducted on 120 new fathers in two groups of 60 cases (admitted to the NICU) and 60 controls (with healthy newborns) referring to the NICU and specialized clinics of Shafizadeh and Ayatollah Rouhani Hospitals in Babol. Participants completed the Edinburgh Postnatal Depression Scale (EPDS) with a score range of (0-30), the Ryff's Psychological Wellbeing Scale (RSPWB-18) with a score range of (18-108), the Connor-Davidson Resilience Scale (CD-RISC) with a score range of (0-100), and the Brief Symptom Inventory (BSI-18) with a score range of (0-72), and the results were reviewed and compared. Findings: In the case group, the mean scores of postpartum depression (12.6±4.12 vs. 8.32±1.64) and psychological distress (54.55±10.48 vs. 44.45±7.03) were significantly higher than in the control group (p<0.001). Moreover, the scores of psychological well-being (80.66±10.18 vs. 86.73±5.80) and resilience (59.81±10.99 vs. 71.05±34.7) were significantly lower (p<0.001). The frequency of postpartum depression symptoms in Edinburgh questionnaire with cut-off point of EPDS≥10 in the group of fathers with infants admitted to the NICU was about 3.5 times that of fathers with healthy infants (46 vs. 12) (p<0.001). The results of logistic regression analysis showed that in new fathers with infants admitted to the NICU, the chance of developing depressive symptoms increases 5-fold (p=0.002, OR=5.217), which increases with age (p=0.046, OR=1.155), but decreases with the increase in resilience (p=0.001, OR=0.865). Conclusion: The results of the study showed that the risk of depression in fathers with infants admitted to the NICU is 5 times higher than fathers with healthy infants. Therefore, timely identification and treatment of postpartum depression is recommended for new fathers with infants admitted to the NICU.